Homework in Icelandic Compulsory schools: Its Amount and Students´, Parents´ and Teachers’ Attitudes - Sigurgeirsson, Ingvar; Björnsdóttir, Amalía (Menntavísindasvið Háskóla Íslands, 2016)
Extensive research on homework has been carried out over the years, but until recently little has been known about its role in Icelandic schools. The purpose of this research was to investigate the attitudes of students, parents and teachers in Iceland towards homework and to address if and how they could be related to factors such as student gender, age and academic abilities. Further, the research looked at the amount of time spent on homework, and students and parents views on parental homework assistance. The research used data from a large scale research project exploring school and classroom practices in twenty Icelandic compulsory schools.Teachers (and other school staff) and parents in the twenty schools participated in surveys and a sample of students in Grades 7‒10 in 14 of the schools (the schools providing lower secondary instruction). Three schools were purposively selected as schools emphasizing differentiated learning, a policy that has been preferred by the Icelandic educational authorities over some time and 17 of the schools were randomly selected. Teachers answered four different surveys in the school year 2009‒2010; the parent survey was conducted in spring 2011 and the student survey in the autumn 2010. There were 7.300 students in the participating schools when data collection started in autumn 2009; 2.119 were randomly selected (two classes in each year group) and answers were obtained from 1.821, or 86%. Questionnaires were sent to the parents of 5.195 students in the twenty schools; one for each home. Answers were obtained from 3.481 parents, or 67%. The response rates in the four school staff surveys were from 80 to 92%. The majority of teachers (and school administrators), or 78%, considered homework as very or rather important and the teachers of the youngest students were the most determinant in this position (86%). The attitudes of teachers across schools varied greatly but no difference was found between attitudes in the schools purposively selected and those selected randomly. ...